Effect of salinity on survival, feed intake and growth of Clarias batrachus (Linn.) fingerlings - Sahoo, S K; Giri, S S; Maharathi, C; Sahu, A K (Indian Journal of Fisheries, 2011)
Effects of different levels of salinity (2, 4, 6, 8 and 10 ppt) on survival, feedintake and growth of freshwater clariid, Clarias batrachus were studied in athirty days laboratory experiment. Although the fingerlings tolerated the saltlevel in water between 0 and 4 ppt, severe mortality was observed beyond 6 ppt after 7-23 days of rearing. No significant (P